Two-point boundary value problems involving reflection of the argument - Chaitan P. Gupta (International Journal of Mathematics and Mathematical Sciences)
Two point boundary value problems involving reflection of the argument are studied. The nonlinearity involved is allowed to cross asymptotically any number of eigenvalues of the associated linear eigenvalue problem as long as those crossings take place in subsets of sufficiently small measure.